2014
DOI: 10.5505/abantmedj.2014.16878
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-lymphocyte ratio in patients with ankylosing spondylitis

Abstract: Amaç: Bu çalışmanın amacı, ankilozan spondilit (AS) hastalarındaki inflamasyon ile nötrofil-lenfosit oranı (NLO) arasındaki ilişkiyi belirlemektir. Yöntem: Ankilozan spondilit tanılı 40 hasta ve 30 sağlıklı gönüllü çalışmaya dahil edildi. Tüm veriler yatan ve poliklinik hasta kayıt veritabanından elde edildi. Tüm olguların Bath Ankilozan Spondilit Hastalık Aktivite İndeksi (BAS-DAI), tam kan sayımı (TKS), CRP ve ESH'ı da kapsıyan ayrın-tılı fizik muayene ve laboratuvar bulguları kaydedildi. Lenfosit ve nötrofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Although the pathogenesis of AS is unknown, some studies have suggested that neutrophils and lymphocytes may play a role in the pathogenesis of AS [1,20]. In the literature, five studies [21][22][23][24][25] showed no significant difference in the NLR when comparing the AS patients with the healthy controls, and similar findings were also obtained with regard to the PLR [21,25,26], which were consistent with the results of this study. However, these results disagreed with the findings of four other studies with regard to the NLR [27][28][29][30] and one study concerning the PLR [24], which might have been related to the involvement of either newly-diagnosed patients with no previous treatment or only patients with active AS in their studies.…”
Section: Discussionsupporting
confidence: 90%
“…Although the pathogenesis of AS is unknown, some studies have suggested that neutrophils and lymphocytes may play a role in the pathogenesis of AS [1,20]. In the literature, five studies [21][22][23][24][25] showed no significant difference in the NLR when comparing the AS patients with the healthy controls, and similar findings were also obtained with regard to the PLR [21,25,26], which were consistent with the results of this study. However, these results disagreed with the findings of four other studies with regard to the NLR [27][28][29][30] and one study concerning the PLR [24], which might have been related to the involvement of either newly-diagnosed patients with no previous treatment or only patients with active AS in their studies.…”
Section: Discussionsupporting
confidence: 90%
“…However, NLR has been studied in some rheumatologic diseases. It was found that NLR levels increased [13, 14] in familial Mediterranean fever patients compared to healthy controls, while NLR levels were not different between healthy individuals and patients with ankylosing spondylitis [15, 16]. However, its higher levels were detected in patients with Behçet’s disease relative to healthy controls [12, 17].…”
Section: Discussionmentioning
confidence: 99%